The edge of chaos is that where consciousness manifests itself through intermittent dynamics - Valeriy Sbitnev (Academia Biology)
Consciousness is a special type of interaction between subjects that is exchanged by lingua quanta (phonemes). A set of lingua quanta composes a thesaurus placed on the edge of chaos. Its library is a memory, modification of which is due to tuning of memristive neural elements scattered in the brain volume. The memristive neural model considers two types of neurons, excitatory and inhibitory, and current leakage at body temperature (T = 310 K). At such temperatures, only heavy ions, such as hydrogen ions (protons), can pass robustly through the water medium of the brain. Robust ion transport involves proton water wires supported by the Grotthuss mechanism. The final aims of the ions are the gap junctions (electric synapses) linking the nearest neurons. Following these observations, a model of excitable nervous tissue was constructed. One-to-one mapping written on the basis of sigmoid curves is capable of reproducing chaotic modes of neural activity, as proved by positive values of the Lyapunov exponent. The edge of chaos is located near the bifurcation boundary dividing chaos and the periodic convulsive activity typical of epileptic discharges. In this region, self-sustained spiral waves occur. Intermittent activity of competing excitatory and inhibitory neurons is observed at the edge of chaos. The intermittent electrical activity of neural tissues is shown by records both from different literature issues and records made by the author and Dr. A. Dudkin on slices of the CA1 field of the hippocampus.